2020
DOI: 10.3390/mi11060566
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Inertial Sorter Coupled with Magnetophoretic Effect for Nonmagnetic Microparticles

Abstract: The sizes of most prokaryotic cells are several microns. It is very difficult to separate cells with similar sizes. A sorter with a contraction–expansion microchannel and applied magnetic field is designed to sort microparticles with diameters of 3, 4 and 5 microns. To evaluate the sorting efficiency of the designed sorter, numerical simulations for calculating the distributions of microparticles with similar sizes were carried out for various magnetic fields, inlet velocities, sheath flow ratios and structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Shao et al [20] found the inner annulus for elevated Re by using the fictitious domain method. Abbas et al [21] mentioned that the equilibrium position (TEP) depends exclusively on Re and k. Recently, inertial microfluidics can precisely separate particles with or without extra external force field by realizing SS effect [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shao et al [20] found the inner annulus for elevated Re by using the fictitious domain method. Abbas et al [21] mentioned that the equilibrium position (TEP) depends exclusively on Re and k. Recently, inertial microfluidics can precisely separate particles with or without extra external force field by realizing SS effect [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Abbas et al [ 21 ] mentioned that the equilibrium position (TEP) depends exclusively on and . Recently, inertial microfluidics can precisely separate particles with or without extra external force field by realizing SS effect [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Common methods include changing the shape of nanoparticles [21], heat radiation [22][23][24][25][26][27], applied electric field [28,29], applied magnetic field [30] and applied electromagnetic field [31]. The heat transfer enhancement by an applied electric or magnetic field is because the electric force or magnetic force on nanoparticles can change the microstructure of nanofluid and movement of nanoparticles [32]. In addition, the interplay among the magnetic field, electric field, flow field and temperature field can result in more severe chaotic convection.…”
Section: Introductionmentioning
confidence: 99%
“…The remainder of this Special Issue includes original research articles on technical innovations of inertial microfluidics for various applications [ 5 , 6 , 7 , 8 ]. Kim et al [ 5 ] report the separation of two freshwater, commercially important, microalgal species, namely, Chlorella Vulgaris and Hematococcus Pluvialis.…”
mentioning
confidence: 99%
“…This highly pure cell purification enabled the expansion of the target organism without the risk of contamination as the minority organism’s culturability of significantly suppressed. In the article by Du et al [ 6 ], on-chip integration of magnetophoresis and inertial focusing was demonstrated for size-based separation of particles with very small size differences (3, 4, and 5 μm). Through systematic numerical and experimental investigations, the optimum conditions to achieve the preferred particle distribution band separation sufficient for separation were determined to be 0.7 × 10 5 A/m, 4, and 0.5 for magnetic intensity, sheath flow ratio, and the contraction–expansion ratio, respectively, while maintaining the sum of particle solution and sheath flow flowrate identical.…”
mentioning
confidence: 99%